Impact of Improved Rice Technology (NERICA varieties) on Income and Poverty among Rice Farming Households in Nigeria: A Local Average Treatment Effect (LATE) Approach - Dontsop Nguezet, Paul M.; Diagne, A.; Okoruwa, V.O.; Ojehomon, V. (2011)
This study examines the impact of the adoption of New Rice for Africa varieties(NERICAs) on income and poverty among Nigerian rice farming households. It usedinstrumental variables estimators to estimate the Local Average Treatment Effect(LATE) of adopting NERICA on income and poverty reduction, using the crosssectional data of 481 farmers from the upland, lowland and irrigated rice ecologies Thefindings reveal a robust, positive and significant impact of NERICA variety adoptionon farm household income and welfare measured by per capita expenditure andpoverty reduction. The empirical results suggest that adoption of NERICA varietieshelped raise household per capita expenditure and income by averages of 49.1% and46.0%, respectively, thereby reducing the probability of adoptive households fallingbelow the poverty line. The study suggests that increased investment in NERICAdissemination, with complementary measures, is a reasonable policy instrument toraise incomes and reduce poverty among rice farming households.